2019
DOI: 10.12659/msm.916815
|View full text |Cite
|
Sign up to set email alerts
|

Two GEO MicroRNA Expression Profile Based High-Throughput Screen to Identify MicroRNA-31-3p Regulating Growth of Medullary Thyroid Carcinoma Cell by Targeting RASA2

Abstract: Background Medullary thyroid carcinoma (MTC), a rare type of thyroid cancer, is a big challenge in clinical treatment. However, the pathogenesis of MTC remains poorly understand. MicroRNAs (miRNAs) were previously demonstrated to be involved in the pathogenesis of MTC, however, the roles of majority of miRNAs in MTC are still undetermined. Material/Methods Two GEO miRNA expression profiles (GSE40807, GSE97070) were downloaded, and the differentially expressed miRNAs (DE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 45 publications
0
7
1
Order By: Relevance
“…[ 11 ] In addition, miRNA-3065-5p was found to be downregulated in melanoma. [ 13 ] Jiang et al confirmed that miRNA-31-3p is downregulated in medullary thyroid carcinoma (MTC), [ 14 ] which is contrast to the present finding. In addition, it was also demonstrated that miRNA-31-3p inhibited MTC cell proliferation by negatively regulating the RASA2 expression.…”
Section: Discussioncontrasting
confidence: 84%
“…[ 11 ] In addition, miRNA-3065-5p was found to be downregulated in melanoma. [ 13 ] Jiang et al confirmed that miRNA-31-3p is downregulated in medullary thyroid carcinoma (MTC), [ 14 ] which is contrast to the present finding. In addition, it was also demonstrated that miRNA-31-3p inhibited MTC cell proliferation by negatively regulating the RASA2 expression.…”
Section: Discussioncontrasting
confidence: 84%
“…Two human MTC cell lines (TT, MZ-CRC-1), and one normal human thyrocyte cell line (NThyy-ori 3.1) were used for the study as TT and MZ-CRC-1 are the two of most widely used MTC-derived cell lines [ 23 25 ]. They were obtained from the Cell Bank of the Chinese Academy of Sciences (Shanghai, China).…”
Section: Methodsmentioning
confidence: 99%
“…RAS gene mutation abrogates its switching capacity leaving it in a constitutively active state, promoting diseased conditions ( 38 , 39 ). It has been shown that the Ras signaling pathway plays significant roles in cellular differentiation, proliferation, apoptosis, and carcinogenesis ( 38 40 ). In addition, Ras can also activate the MAPK and PI3K/AKT pathways, leading to the progression of thyroid cancer ( 40 ).…”
Section: Discussionmentioning
confidence: 99%